Involuntary Childlessness at Work: Experiences of Emotion Work, Unfair Marginalization and Inadequacy - Mård, Mika (Nordic Journal of Working Life Studies, 2021)
This article presents and analyzes experiences of involuntary childlessness at work and, through that, attempts to increase our understanding of emotional and silenced experiences in organizations. While primarily being an exploratory study with a purpose to get an initial glimpse into working life through involuntary childless individuals’ point of view, this article also engages with Arlie Hochschild’s (1979, 1983) conceptualization of emotion work to analyze experiences of involuntary childlessness at work. The empirical data used in this paper are mainly collected through an anonymous diary studies method in Finland, and thematically presented in this article in three segments where three categories of emotion work related to involuntary childlessness are analyzed and discussed. In addition to offering an initial glimpse of involuntary childlessness at work, this paper hence contributes with a demonstration and analysis of the multifaceted emotion work related to these experiences.